2017
DOI: 10.1016/j.ajog.2017.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of USPSTF recommendations for aspirin for prevention of recurrent preeclampsia

Abstract: BACKGROUND The U.S. Preventive Services Task Force (USPSTF) recommends low-dose aspirin for the prevention of preeclampsia among women at high risk for primary occurrence or recurrence of disease. Recommendations for the use of aspirin for preeclampsia prevention were issued by the USPSTF in September 2014. OBJECTIVES To evaluate the incidence of recurrent preeclampsia in our cohort before and after the USPSTF recommendation for aspirin for preeclampsia prevention. STUDY DESIGN This is a retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 41 publications
0
35
1
Order By: Relevance
“…To date, the only therapeutic option for the prevention of PE is aspirin use. Thus, aspirin given at a daily dose of 75–150 mg from the end of the first trimester to the end of pregnancy may reduce the risk of PE onset by 30% . In women with a history of early onset PE (<34 WG), the gestational time is most often prolonged by approximately five weeks in the subsequent pregnancy .…”
Section: Pathophysiology Of Preeclampsiamentioning
confidence: 99%
“…To date, the only therapeutic option for the prevention of PE is aspirin use. Thus, aspirin given at a daily dose of 75–150 mg from the end of the first trimester to the end of pregnancy may reduce the risk of PE onset by 30% . In women with a history of early onset PE (<34 WG), the gestational time is most often prolonged by approximately five weeks in the subsequent pregnancy .…”
Section: Pathophysiology Of Preeclampsiamentioning
confidence: 99%
“…From economical perspectives, whether aspirin prophylaxis is for (i) only test‐positive individuals on a formalized screening test algorithm, (ii) only those with major risk factors or (iii) all women without assessment of prior risks remains to be explored . It is advisable to offer aspirin in women with a prior history of pre‐eclampsia because it reduces the recurrence by 30% …”
Section: Resource Implications Of Pre‐eclampsia Prediction and Prophymentioning
confidence: 99%
“…(7,8) In obstetrics, low-dose aspirin has been shown to be effective in preventing preterm preeclampsia, with delivery at <37 weeks' gestation, in women at risk. (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) The ASPRE (27) The latest systematic review and meta-analysis demonstrated that the reduction in the rate of preterm preeclampsia was confined to the subgroup in which aspirin was initiated at ≤16 weeks' gestation and at a daily dose of ≥100 mg (relative risk [RR], 0.33; 95% CI, 0.19-0.57). (20) Evidence suggests that pre-conception or early administration of low-dose aspirin might improve endometrial growth, placental vascularization and organogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Publication bias was not assessed due to the small number of included studies. Statistical analysis was performed using Stata release 14.0 (StataCorp, College Station, TX).…”
mentioning
confidence: 99%